Analysis of quality and framing in the journalistic coverage of Machu Picchu as the first carbon neutral tourist destination - Muguerza Lescano, Mario Juan (2023)
The article analyzes the journalistic coverage of the Peruvian cyber media on the recognition of the Historic Sanctuary of Machu Picchu as the first carbon neutral tourist attraction in the world. The main objective was to study the informative quality and the frames that the Peruvian News Agency Andina, El Peruano, El Comercio and La República used in digital articles, from October 2, 2020 to January 7, 2022. Through a mixed approach, 48 notes were examined. The results showed that the cybermedia lack specialized sections on environmental issues; there is a lack of dynamism in the use of genres, structures and narrative levels; and episodic and issue frames were more employed. The researchers concluded that positive environmental news is not exposed by the media as much as dramatic events.